THE ETIOLOGY, PREVENTION, AND MODERN APPROACHES TO THE TREATMENT OF DENTAL CARIES (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Dental caries remains one of the most widespread chronic diseases affecting people of all ages worldwide. Despite significant advances in preventive dentistry and restorative techniques, caries continues to pose a major public health challenge due to its multifactorial nature and close association with lifestyle, socioeconomic factors, and oral hygiene practices. This scientific article aims to analyze the etiology, pathogenesis, risk factors, preventive strategies, and modern approaches to the diagnosis and treatment of dental caries. Special attention is given to contemporary preventive measures, including fluoride use, dietary control, and patient education. The article emphasizes the importance of early diagnosis and integrated prevention programs in reducing the global burden of dental caries.